Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Pembuatan Batik Ecoprint untuk Meningkatkan Kreativitas dan Pendapatan di Kabupaten Magetan - Susanti Susanti; Heny Subandiyah; Han Tantri Hardini; Renny Dwijayanti (Abimanyu : Jornal of Community Engagement, 2026)
This community service program was motivated by the low skills and income levels of housewives in Magetan Regency, despite the region’s rich natural resources. The purpose of this activity was to enhance creativity and economic independence among housewives through environmentally friendly batik ecoprint training. The implementation methods included preparation, socialization, theoretical and practical training, mentoring, and evaluation. Participants were trained to use leaves and flowers as natural dyes in the batik-making process, accompanied by entrepreneurship and product marketing sessions. The results showed a significant improvement in participants’ knowledge, skills, and motivation to develop independent ecoprint-based businesses. In conclusion, the training successfully increased creativity, fostered entrepreneurial spirit, and contributed to family income growth and the development of the local creative economy.